The increasing prevalence of Parkinson's disease in Estonia. (29th April 2018) - Kadastik‐Eerme, L.; Taba, N.; Asser, T.; Taba, P.
Abstract : Objectives: A previous epidemiological study of Parkinson's disease (PD) in the county of Tartu, Estonia, found an adjusted prevalence rate of 152/100 000 persons. We aimed to determine PD prevalence almost 20 years later, as well as evaluate any dynamic changes in disease frequency compared to the first study. Methods: A cross‐sectional, community‐based study was conducted over 2010‐2016 in the county of Tartu, Estonia. Multiple case‐finding sources, including information from neurologists, family doctors, the local PD Society, nursing institutions, and the database of the Estonian Health Insurance Fund were used to identify patients with PD of all ages. Results: Total crude PD prevalence was 283 and age‐adjusted prevalence (standardized to the 2014 age structure of the Estonian population) 314/100 000. No significant differences in age‐adjusted prevalence rates were found between men and women, nor people living in urban and rural areas. After adjustment to the same standard population used in the previous prevalence study, the overall age‐adjusted prevalence rate was 197/100 000. Patients in the current study were older and often had a more severe form of PD and a longer disease duration, compared to those reported in the first epidemiological study 20 years ago. Conclusions: The age‐specific crude rates in oldest age‐groups have risen substantially, and the age‐adjusted prevalence has moderately increased compared to 20 years ago in Estonia. We hypothesize that the increased life expectancy of the Estonian population and improved diagnosis of PD contributed most to the increase in disease frequency.